Socio-Economic Profile and Knowledge Level of Dairy Farmers about Improved Dairy Farming Practices in Jammu District - Shafiqi, Shazia; Kumar, Pranav; Khandi, S A; Bhadwal, M S (Journal of Agricultural Extension Management, 2019)
The present investigation was conducted in Jammu district of J & K state withthe objective to assess the knowledge level of dairy farmers about improveddairy farming practices. The data were collected from 120 respondents,belonging to R.S Pura and Marh block, through personal interview. The studyrevealed that a majority of the respondents were in the middle age group andmajority had poor education. The respondents were mainly marginal farmerswith land holding of less than 2.5 acres and a herd size of 2-4 animals. Most ofthe dairy farmers had low level of social participation and extension contact.However, they had medium level of mass media exposure. The study revealedthat majority of the respondents (71.66%) had medium level of knowledgeabout improved dairy farniing practices. The dairy farmers had greaterknowledge about feeding practices (73.28%) and least about improvedbreeding practices (48.22%). It is suggested that efforts may be made toincrease the literacy rate of farmers so that they can utilize the availableliterature for improving their knowledge as well as skills. Mass media alsoneed to be utilized for transfer of improved dairy farming practices to farmersfor enriching their knowledge.